Post-disaster relief operations considering psychological costs of waiting for evacuation and relief resources. Issue 2 (7th February 2017) - Hu, Zhi-Hua; Sheu, Jiuh-Biing; Yin, Yu-Qi; Wei, Chen
Abstract : After a disaster, a huge number of homeless victims should be evacuated from disaster sites to temporary shelters. However, because the evacuation capacity is insufficient, victims must be evacuated in batches and some of them must wait for evacuation at disaster sites; even the victims who have been evacuated to shelters must wait for resources, because the relief resources (e.g. tents) are insufficient. The psychological penalty cost perceived by victims may increase when they are waiting for evacuation at disaster sites or for relief resources at shelters, whereas psychological interventions can decrease the magnitude of the perceived psychological cost. Novel mathematical programs were developed for multi-step evacuation and sheltering under minimization of monetary and psychological penalty costs. By developing typical scenarios, the resource scarcity and psychological severity are investigated. With Wenchuan County (the epicenter of the 2008 Sichuan earthquake) as the test case, the influence and the sensitivity of parameters, tradeoff between monetary and psychological costs, and the effects of various scenarios are assessed using six experiments. Analytical results reveal the complexity and managerial insights by applying the proposed models to post-disaster evacuation and sheltering.